Molecular characterization of Cryptosporidium isolates from calves in Argentina - Tomazic, Mariela Luján (2013)
Cryptosporidiosis is responsible for significant fatalities of neonatal calves, resulting in substantial economic loss in dairy farming in several countries. Additionally, the high shedding of environmentally resistant oocysts by calves promotes contamination of drinking water and facilitates outbreaks of cryptosporidiosis in humans. Here we report on the Cryptosporidium species and GP60 subtypes of 45 calves originating from the Humid Pampa, the main productive dairy farming area of Argentina. Polymerase chain reaction (PCR)-restriction fragment length polymorphism (RFLP) analysis of the 18S rRNA gene was done to determine the infecting Cryptosporidium species and only Cryptosporidium parvum was detected. Subtyping by sequence analysis of the GP60 gene revealed 6 different alleles all pertaining to the zoonotic IIa family. Of these, IIaA23G1R1 represents a novel IIa subtype. Other identified subtypes, IIa18G1R1, IIaA20G1R1, IIaA21G1R1, and IIaA22G1R1 have been recognized in very few studies and/or with low frequencies. Interestingly, different alleles prevailed in the provinces of Buenos Aires (IIaA17G1R1 and IIaA21G1R1), Santa Fe (IIaA23G1R1), and Cordoba (IIaA20G1R1 and IIaA21G1R1), and different allele distribution patterns were observed. Subtypes IIaA18G1R1 and IIaA17G1R1, the latter often found in this study, are strongly implicated in zoonotic transmission, suggesting that calves may represent a potential source for human cryptosporidiosis in this region. This is the first published report of a molecular analysis of Cryptosporidium infection in dairy and beef calves from Argentina.